(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
The use of rigid materials to adequately support the joints and exert corrective forces that control the deformities of the bones is a key pre-requisite in prescribing custom-fit orthoses in rehabilitation treatment. Traditional orthotic materials are heavy in weight, bulky and completely unbreathable, which reduce the quality of life, comfort and satisfaction with the orthosis and result in poor patient compliance and even significant curve progression. The present study aims to explore the use of carbon fibre, fibreglass and fibreglass-carbon composites to develop an orthotic brace. Apart from the mechanical testing, the thermal discomfort properties and in-brace pressure with the use of traditional orthotic braces were also examined. Compared to traditional thermoplastic materials, the fibre composite materials have good resistance to breakage, more flexibility in bending with improved water vapour transmission, air permeability and thermal conductivity which advance orthosis use and wear comfort. An increase in the number of layers of composite materials increases the bending rigidity and also considerably augments the corrective forces. The corrective forces and ⁄ or support that control the deformity of joints or bones can therefore be adjusted by altering the number of layers of composites. The use of fibre composite materials in orthoses not only improves the prevailing problems of wear discomfort, but also facilitates the control of corrective forces, thus enhancing the quality of orthotic intervention.